Character Traits Of Effective Executives: A Phenomenological Study Of Ceos In Ghana - Remy Nyukorong; William Quisenberry (European Scientific Journal, ESJ, 2016)
Leadership in organizations has been widely studied in the literature. However, scant research could be found exploring the critical personality characteristics business executives need to have in order to lead corporate organizations more effectively. This qualitative, phenomenological study was designed to investigate the lived experience of top-level business leaders in leadership roles. Ten Chief Executive Officers of Ghana Club 100 were interviewed and told their experience as leaders. The email and face-to-face interview transcripts were coded and analyzed for themes. The following personality attributes emerged from the study which were found to support and promote strong executive effectiveness: integrity, forward-looking, selfconfidence, emotional intelligence and maturity, and caring for others. The study significance provides information to Board of Directors of Ghanaian Corporations in the selection, promotion, and training of executive-level managers, and potentially lower the costs associated with losing highpotential executive leaders. The study findings could also help business schools and management consultants to focus better on preparing business leaders for the future. A major limitation of the study was the small sample size, which may require caution in generalizing the findings to the entire population. The current study is one of the first to be carried out in Ghana on leader personality traits.